#TITLE_ALTERNATIVE# - SATRIJO (NIM 23194001); Pembimbing: Prof.Dr.Ir.H. Darmawan Harsokoesoemo, DJOELI
Carrying natural sources from a bottom of the sea to sea surface has become mandatory. Since more natural sources that have great demand and a quantity of sources in the land have become rare. Especially, crude oil and natural gas. This demand directs on underwater exploitation which the depth become deeper. One of the important component in underwater exploitation which more than 100 m is marine riser. This component like a pipe that is verticaly effected from bottom of the sea to the sea surface. Its functions are for carrying mine deposit, and as guide boning device. As consequences, this structure should be capable to support load due to sea wave, current, wind, and the weight of structure and fluid in the pipe. In this thesis, the riser has been modelled as pipe which is supported by simple support and loaded only by sea wave. The solution of its dynamic responses has been solved by steady-state frequency domain analysis. The discritization of structure was conducted by Galerkin method. The result of this solution is a distribution of displacement amplitude along a pipe and a distribution of stress amplitude. The model that has been studied in this thesis consist of two kinds of model, namely, the model which not involved with interaction between structure and fluid, and the model which involved with interaction between structure and fluid. In the first model , the differential equation is linear, but in the second model the differential equation is non linear. In the second model, the simplification was carried out by linearisation technique which substitute a equivalen damping term.